Design guidelines for titania-silica-alumina ceramics with tuned anatase to rutile transformation. Issue 5 (1st April 2019) - Feltrin, J.; De Noni, A.; Hotza, D.; Frade, J.R.
Abstract: Titania-based ceramics with adjustable anatase-rutile fractions were obtained by milling of anatase, quartz and corundum precursors, uniaxial pressing and firing at 1100 °C. The influence of silica and alumina, combined with milling time and compaction pressure, was studied by design of experiments. The L9 orthogonal array with a three-level noise factor was employed. Firing of pure titania at 1100 °C yielded complete anatase to rutile transformation (ART), whereas stabilized samples show that an optimum amount of 9% silica and 33% alumina reduces phase transformation to only about 5 wt% rutile. An extended correlation matrix combined with analysis of variance (ANOVA) was applied to assess the combined effects of quartz, alumina, milling time and uniaxial compressing pressure on relative density, and anatase to rutile transformation. Results show absence of ART after milling, and controlled partial conversion of anatase to rutile after firing. Very good fitting was obtained by multivariate analysis on considering first and second order terms for dependence on silica contents and interactions between silica and each of the remaining factors, including milling time. This empirical dependence could be interpreted on a sound physicochemical basis, allowing the prediction of suitable compositions and processing conditions to obtain rutile-free samples by conventional ceramic processing, and to design ceramic samples with controlled fractions of anatase and rutile.